Uncaria tomentosa extract exerts antimicrobial activity against boar seminal bacteria and influences sperm resilience under different conditions - Scaringi, Maria; Pintus, Eliana; Nový, Pavel; Božiková, Katerina; Maršík, Petr; Ros-Santaella, Jose Luis (Frontiers in Veterinary Science, 2025)
Uncaria tomentosa (UT) or cat's claw, is a vine belonging to the Rubiaceae family and native to South and Central America. Various parts of the plant, including bark, showed many therapeutic activities (e.g., antioxidant and antibacterial), but the in vitro effects on gametes have still not been investigated. During boar semen storage for artificial insemination purposes, oxidative stress and bacterial contamination negatively affect sperm quality. In this study, we evaluated the tolerance of boar sperm to UT ethanolic extract at four concentrations (1.6 to 0.025 μg/mL). The analyses were carried out on sperm samples under oxidative stress, induced by H2O2 and Fe2+/Ascorbate, and during 96 h of semen storage at 17°C. The antibacterial activity of the extract (1,024 to 8 μg/mL) was tested against commercial strains and bacteria isolated from the semen. The treatments ranging from 0.4 to 0.025 μg/mL protected sperm membrane (p < 0.05) and preserved some kinetic parameters in samples under oxidative stress (Fe2+/Ascorbate). During semen storage, the extract did not show any cytotoxicity, and mean values of some sperm parameters were higher than the control group, although not significant (p > 0.05). All tested Gram-positive bacteria exhibited growth inhibition. The most frequently isolated Gram-negative bacteria from semen (i.e., Citrobacter koseri, Pseudomonas aeruginosa, Stenotrophomonas maltophilia) also showed complete growth inhibition, while the remaining strains showed a partial decrease in growth. Taken together, our findings show that Uncaria tomentosa is a promising plant-based additive for boar semen storage.